Deformation-free geometric recrystallisation in a metastable β-Ti alloy produced by selective laser melting - Ahmad Zafari; Edward W. Lui; Kenong Xia (Materials Research Letters, 2020)
Super-transus heat treatments conducted on an additively manufactured body-centred-cubic β-Ti alloy led to the formation of equiaxed β grains from an initially columnar structure. The grain structure was transformed thanks to a combination of Plateau-Rayleigh instability and grain growth driven by reduction in grain boundary surface area. This is a new type of geometric recrystallisation with no deformation involved. Other mechanisms proposed based on either deformation-induced recrystallisation or martensitic decomposition are dismissed owing to low dislocation density and absence of martensitic transformation in the alloy studied.